A century and a half of research on the evolution of insect flight. Issue 4 (July 2018) - Alexander, David E.
Abstract: The gill and paranotal lobe theories of insect wing evolution were both proposed in the 1870s. For most of the 20th century, the paranotal lobe theory was more widely accepted, probably due to the fundamentally terrestrial tracheal respiratory system; in the 1970s, some researchers advocated for an elaborated gill ("pleural appendage") theory. Lacking transition fossils, neither theory could be definitively rejected. Winged insects are abundant in the fossil record from the mid-Carboniferous, but insect fossils are vanishingly rare earlier, and all earlier fossils are from primitively wingless insects. The enigmatic, isolated mandibles of Rhyniognatha (early Devonian) hint that pterygotes may have been present much earlier, but the question remains open. In the late 20th century, researchers used models to study the interaction of body and protowing size on solar warming and gliding abilities, and stability and glide effectiveness of many tiny adjustable winglets versus a single, large pair of immobile winglets. Living stoneflies inspired the surface-skimming theory, which provides a mechanism to bridge between aquatic gills and flapping wings. The serendipitously discovered phenomenon of directed aerial descent suggests a likely route to the early origin of insect flight. It provides a biomechanically feasible sequence from guided falls to fully-powered flight. Graphical abstract: Highlights: Gill and paranotal lobe theories of wing evolution were both proposed in the 1870s. Paranotal lobe theory has had wider acceptance, but gill theory has had prominent supporters. The incomplete fossil record is little help: there is no Archaeopteryx for insects. "Bounded ignorance" approach has brought useful insights from biomechanics and behavior. Wide occurrence of directed aerial descent prompts review of pressures favoring flight.